Difficulties in the Treatment of Oral Lichen Planus in a Systemically Compromised Patient: Case Report and Review of the Literature - Boza Oreamuno, Yadira V. (2021)
Oral lichen planus (OLP) is a chronic inflammatory and immune-mediated disease that presents as bilateral, symmetrical oral lesions with three main clinical presentations: reticular, atrophic, and erosive. It is clinically characterized by pain, burning sensation, and discomfort for sufferers. Currently OLP is classified as a potentially malignant oral disorder. It has been associated with numerous systemic connotations such as diabetes mellitus, hypertension, metabolic syndrome, thyroid diseases, psychosomatic ailments, chronic liver disease, and gastrointestinal diseases. Diagnosis is made by clinical and histological examinations. It is a non-curable disease, the treatments are applied seeking the reduction or disappearance of the associated pain, as well as improving the clinical appearance of erosive-ulcerative lesions. The objective of this work was to present through a clinical case the difficulties in the treatment of OLP in a systemically compromised patient, highlighting the comprehensive assessment of the same, failed pharmacological therapies, until the symptomatology diminished and the patient's quality of life improved.